Plastic film mulching and microplastics impact soil nitrogen processes - Jinrui ZHANG; Kai WANG; Tong ZHU; Tao CHENG; Rui JIANG; Xuejun LIU (Frontiers of Agricultural Science and Engineering)
Plastic film mulching (PFM) significantly enhances crop yield and quality by increasing soil temperature, reducing water evaporation and optimizing nutrient cycling. However, improper management of plastic film residues has led to microplastic pollution in farmland, posing a major challenge to sustainable agricultural development. The accumulation of microplastics in soil not only affects soil structure but also profoundly impacts crop growth and ecosystem stability by altering nitrogen-related microbial activities and nitrogen (N) cycling processes. This review synthesizes the effects of PFM and microplastics on soil N pools and cycling, exploring their mechanisms in plant N uptake, microbial immobilization, gaseous emissions (e.g., NH3 and N2O), and N transformation processes (e.g., N fixation, assimilation, mineralization, nitrification and denitrification). Research indicates that PFM and microplastics significantly influence N processes by modifying soil physicochemical properties and microbial community structure, although their effects vary depending on plastic type, environmental conditions and crop growth stages. Future studies should further investigate the long-term ecological impacts of microplastics in complex natural environments and employ advanced statistical methods and models to quantify their dynamic effects on N cycling.